The Effects of Furosemide on Oxygenation in Mechanically Ventilated Children with Bronchiolitis - Kulkarni, Mandar; Slain, Katherine N.; Rotta, Alexandre T.; Shein, Steven L. (Journal of Pediatric Intensive Care, 2020)
Fluid balance management, including diuretic administration, may influence outcomes among mechanically ventilated children. We retrospectively compared oxygenation saturation index (OSI) before and after the initial furosemide bolus among 65 mechanically ventilated children. Furosemide was not associated with a significant change in median OSI (6.25 [interquartile range: 5.01–7.92] vs. 6.06 [4.73–7.54], p = 0.48), but was associated with expected changes in fluid balance and urine output. Secondary analysis suggested more favorable effects of furosemide in children with worse baseline OSI. The reported common use of furosemide by pediatric intensivists obligates further study to better establish its efficacy, or lack thereof, in mechanically ventilated children.
Keywords: bronchiolitis; mechanical ventilation; diuretics